Alteration of cell wall xylan acetylation triggers defense responses that counterbalance the immune deficiencies of plants impaired in the β‐subunit of the heterotrimeric G‐protein. (15th September 2017) - Escudero, Viviana; Jordá, Lucía; Sopeña‐Torres, Sara; Mélida, Hugo; Miedes, Eva; Muñoz‐Barrios, Antonio; Swami, Sanjay; Alexander, Danny; McKee, Lauren S.; Sánchez‐Vallet, Andrea; Bulone, Vincent; Jones, Alan M.; et al.
Summary: Arabidopsis heterotrimeric G‐protein complex modulates pathogen‐associated molecular pattern‐triggered immunity (PTI) and disease resistance responses to different types of pathogens. It also plays a role in plant cell wall integrity as mutants impaired in the Gβ‐ ( agb1‐2 ) or Gγ‐subunits have an altered wall composition compared with wild‐type plants. Here we performed a mutant screen to identify suppressors of agb1‐2 ( sgb ) that restore susceptibility to pathogens to wild‐type levels. Out of the four sgb mutants ( sgb10–sgb13 ) identified, sgb11 is a new mutant allele of ESKIMO1 ( ESK1 ), which encodes a plant‐specific polysaccharide O ‐acetyltransferase involved in xylan acetylation. Null alleles ( sgb11/esk1‐7 ) of ESK1 restore to wild‐type levels the enhanced susceptibility of agb1‐2 to the necrotrophic fungus Plectosphaerella cucumerina BMM ( PcBMM ), but not to the bacterium Pseudomonas syringae pv. tomato DC3000 or to the oomycete Hyaloperonospora arabidopsidis . The enhanced resistance to PcBMM of the agb1‐2 esk1‐7 double mutant was not the result of the re‐activation of deficient PTI responses in agb1‐2 . Alteration of cell wall xylan acetylation caused by ESK1 impairment was accompanied by an enhanced accumulation of abscisic acid, the constitutive expression of genes encoding antibiotic peptides and enzymes involved in the biosynthesis of tryptophan‐derived metabolites, and the accumulation of disease resistance‐related secondary metabolites and different osmolites. These esk1 ‐mediated responses counterbalance the defective PTI and PcBMM susceptibility of agb1‐2 plants, and explain the enhanced drought resistance of esk1 plants. These results suggest that a deficient PTI‐mediated resistance is partially compensated by the activation of specific cell‐wall‐triggered immune responses. Significance Statement: The plant heterotrimeric G protein complex is an essential component of Pathogen Associated Molecular Pattern‐triggered immunity (PTI) and of plant disease resistance to several types of pathogens. We found that modification of the degree of xylan acetylation in plant cell walls activates PTI‐independent resistance responses that counterbalance the hypersusceptibility to particular pathogens of plants lacking the heterotrimeric G subunit. These data demonstrate that immune deficient response can be partially compensated by the activation of cell wall‐triggered immunity that confers specific disease resistance.